Mining candidate genes for maize plant height based on a GWAS, Meta-QTL, and WGCNA - Qian, Fu; Zhang, Zhanqin; Chen, Shubin; Sang, Zhiqin; Li, Weihua (Frontiers in Plant Science, 2025)
IntroductionIn maize, plant height (PH) is one of the most important agronomic traits that directly influences planting density and yield. Therefore, identifying candidate genes related to PH will help manipulate maize yield indirectly.MethodsThe present research carried out a genome-wide association study (GWAS) of PH using a natural population of 580 maize inbred lines. Further, after collecting the published transcriptome data of maize B73, tissue-specific gene co-expression modules related to PH were generated using weighted gene co-expression network analysis (WGCNA). Furthermore, a meta-analysis of the already reported PH-related quantitative trait loci (QTLs).ResultsThe integrated analysis of the results based on the different approaches screened three candidate genes: Zm00001d031796, encoding AP2-EREBP transcription factor 172; Zm00001d009918, encoding Phytochrome A-associated F-box protein; and Zm00001d042454, encoding plastid specific ribosomal protein 4.